2019
DOI: 10.14738/assrj.61.5963
|View full text |Cite
|
Sign up to set email alerts
|

Effects of taxpayer compliance with taxpayer consciousness as intervening variable

Abstract: This study analyzes (1) the effect of tax authorities services on taxpayer awareness; (2) the effect of tax sanctions on taxpayer awareness; (3) the effect of tax audits on taxpayer awareness; (4) the effect of taxpayer awareness on mandatory compliance; (5) the effect of tax authorities services on taxpayer compliance; (6) the effect of sanctions on taxpayer compliance; (7) the effect of tax audits on taxpayer compliance; (8) the role of mediating the awareness of taxpayers in the influence of tax authorities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
1
0
0
1
Order By: Relevance
“…So, it can be concluded that the taxpayer's awareness reinforces the positive influence of tax audits on taxpayer compliance, and based on these statistical results it can be concluded that the tenth hypothesis is accepted, which shows a statistical t value of 2.160 greater than the value (t> 1.96). This research in line with the research ofLisa, 2018;Dwi, 2017;Lallo, 2019;Situmorang, 2019; Al-Maghrebi et all, 2016.…”
supporting
confidence: 89%
“…So, it can be concluded that the taxpayer's awareness reinforces the positive influence of tax audits on taxpayer compliance, and based on these statistical results it can be concluded that the tenth hypothesis is accepted, which shows a statistical t value of 2.160 greater than the value (t> 1.96). This research in line with the research ofLisa, 2018;Dwi, 2017;Lallo, 2019;Situmorang, 2019; Al-Maghrebi et all, 2016.…”
supporting
confidence: 89%
“…Nhân tố thể chế đóng một vai trò quan trọng trong việc thách thức các quyết định tuân thủ thuế của NNT thông qua tính răn đe và trừng phạt, tính hiệu quả của chính sách thuế, đơn giản hóa công tác thuế bằng các quy trình, thủ tục mới; cung cấp các công tác tư vấn, hỗ trợ người nộp thuế; giải quyết khiếu nại kịp thời, chính đáng và dịch vụ hiệu quả cho NNT (Lalo, 2019).…”
Section: Mô Hình Nghiên Cứu đề Xuấtunclassified